TMEM16A deficiency: a potentially fatal neonatal disease resulting from impaired chloride currents. Issue 4 (2nd June 2020) - Park, Julien H; Ousingsawat, Jiraporn; Cabrita, Inês; Bettels, Ruth E; Große-Onnebrink, Jörg; Schmalstieg, Christian; Biskup, Saskia; Reunert, Janine; Rust, Stephan; Schreiber, Rainer; Kunzelmann, Karl; Marquardt, Thorsten
Abstract : Introduction: TMEM16A is a calcium-activated chloride channel expressed in various secretory epithelia. Two siblings presented in early infancy with reduced intestinal peristalsis and recurrent episodes of haemorrhagic diarrhoea. In one of them, the episodes were characterised by hepatic pneumatosis with gas bubbles in the portal vein similar to necrotising enterocolitis of the newborn. Methods: Exome sequencing identified a homozygous truncating pathogenic variant in ANO1 . Expression analysis was performed using reverse transcription PCR, western blot and immunohistochemistry. Electrophysiological and cell biological studies were employed to characterise the effects on ion transport both in patient respiratory epithelial cells and in transfected HEK293 cells. Results: The identified variant led to TMEM16A dysfunction, which resulted in abolished calcium-activated Cl − currents. Secondarily, CFTR function is affected due to the close interplay between both channels without inducing cystic fibrosis (CF). Conclusion: TMEM16A deficiency is a potentially fatal disorder caused by abolished calcium-activated Cl − currents in secretory epithelia. Secondary impairment of CFTR function did not cause a CF phenotyp, which may have implications for CF treatment.